Elevated fetal haemoglobin is a predictor of better outcome in MDS/AML patients receiving 5‐aza‐2′‐deoxycytidine (Decitabine). (1st December 2016) - Lübbert, Michael; Ihorst, Gabriele; Sander, Philipp N.; Bogatyreva, Ljudmila; Becker, Heiko; Wijermans, Pierre W.; Suciu, Stefan; Bissé, Emmanuel; Claus, Rainer
Summary: Although azanucleoside DNA‐hypomethylating agents (HMAs) are routinely used for the treatment of myelodysplastic syndrome/acute myeloid leukaemia (MDS/AML), very few outcome predictors have been established. Expression of the β‐like globin gene locus is tightly regulated by DNA methylation, is HMA‐sensitive in vitro, and fetal haemoglobin (HbF) expression is under study as a potential biomarker for response of MDS patients to azacitidine. We determined HbF expression in 16 MDS and 36 AML patients receiving decitabine (DAC). Pre‐treatment HbF was already elevated (>1·0% of total haemoglobin) in 7/16 and 12/36 patients, and HbF was induced by DAC in 81%/54% of MDS/AML patients, respectively. Elevated pre‐treatment HbF was associated with longer median overall survival (OS): 26·6 vs. 8·6 months for MDS (hazard ratio [HR] 8·56, 95% confidence interval [CI] 1·74–42·49, P  = 0·008, with similarly longer progression‐free and AML‐free survival), and 10·0 vs. 2·9 months OS for AML (HR 3·01, 95% CI 1·26–7·22, P  = 0·014). In a multivariate analysis, the prognostic value of HbF was retained. Time‐dependent Cox models revealed that the prognostic value of treatment‐induced HbF induction was inferior to that of pre‐treatment HbF. In conclusion, we provide first evidence for in vivo HbF induction by DAC in MDS/AML, and demonstrate prognostic value of elevated pre‐treatment HbF, warranting prospective, randomized studies.